INVESTIGATING STUDENTS' WRITING PROCESS IN DESCRIPTIVE WRITING (A case study in one state university in Bandung) - Permadi, Andrian (2014)
This study aims to investigate students' writing process in writing a descriptive text in one state university in Bandung. This study used a case study research design which employed four data collection techniques, i.e. classroom observation, questionnaire, semi-structured interview, documentation and analysis of students' descriptive texts. The participants of the study were 14 undergraduate students who were studying in their first year majoring in English. The study revealed several findings. Firstly, the results of classroom observation, questionnaire, and semi-structured interview data showed that all participants, who were high, middle and low achiever students, had gone through three main stages, pre-writing stage, writing/drafting stage, and post-writing stage, in their writing process. Secondly, it was also found that the high and middle achiever students conducted the same activities throughout their writing process, which were reading, outlining, mind mapping, writing a written guideline, planning, brainstorming, inquiring, formulating, monitoring, drafting, conferencing, evaluating, revising, sharing, and publishing. While, the low-achiever students conducted different activities compared to the high and middle achiever students. Those activities were brainstorming, writing the first draft in bahasa Indonesia, revising, conferencing, and publishing. Furthermore, the analysis of students' descriptive texts (final draft) using Systemic Functional Grammar revealed that the high and middle achiever students were able to produce descriptive texts that fulfilled the required schematic structure, organization, purpose and linguistic features of a descriptive type of writing, while the low achiever students were not. These findings showed that the activities performed by the high and middle achiever students at the pre, writing/drafting, post writing stages gave beneficial contribution toward the quality of their descriptive texts. On the other hand, the activities conducted by the low achiever students at those stages did not give any significant contribution toward the quality of their descriptive texts. Based on these findings, it is suggested that the curriculum or syllabus should focus more on the nature of students' writing process where different (writing) activities have occurred, as they are able to influence the quality of students' writing. In addition, specific writing courses or programs are also needed both for students, specifically for low achievers, and teachers or lecturers in order to accommodate students with their writing difficulties and tasks. Keywords: writing process (pre writing stage, writing/drafting stage, post writing stage, and descriptive texts. Penelitian ini bertujuan untuk mengamati proses menulis subjek penelitian dalam membuat teks deskriptif di salah satu perguruan tinggi negeri di Bandung. Penelitian ini menggunakan metode studi kasus dengan empat teknik pengumpulan data yaitu; observasi, kuesioner, wawancara semi terstruktur, dokumentasi, dan analisis teks. Subjek penelitian dalam penelitian ini adalah empat belas mahasiswa S1 jurusan bahasa Inggris semester satu. Hasil penelitian ini terdiri dari beberapa temuan. Pertama, hasil observasi kelas, kuesioner, dan wawancara semi terstruktur menunjukkan bahwa semua mahasiswa yang dibagi ke dalam kategori pemelajar tingkat lanjut (high-achievers), pemelajar tingkat menengah (middle-achievers), dan pemelajar tingkat dasar (low-achievers) telah melalui tiga tahapan dalam proses menulis, yaitu; tahap pra menulis (pre writing stage), tahap menulis (writing/drafting stage), dan tahap pasca menulis (post writing stage). Kedua, ditemukan juga bahwa para pemelajar tingkat lanjut (high-achievers) dan pemelajar tingkat menengah (middle-achievers) melakukan tahapan menulis yang sama, yaitu; reading, outlining, mind mapping, writing a written guideline, planning, brainstorming, inquiring, formulating, monitoring, drafting, conferencing, evaluating, revising, sharing, dan publishing. Namun, para pemelajar tingkat dasar (low-achievers) melakukan tahapan menulis yang berbeda, yaitu membuat kerangka tulisan dalam bahasa Indonesia, revising, conferencing, dan publishing. Ketiga, hasil analisis teks deskriptif para pemelajar dengan menggunakan teknik analisis tata bahasa fungsional sistemik menunjukkan bahwa pemelajar tingkat lanjut (high-achievers) dan pemelajar tingkat menengah (middle-achievers) mampu menghasilkan teks deskriptif yang sesuai dengan skema struktur, organisasi, tujuan, dan ciri-ciri kebahasaan tulisan deskriptif, sedangkan para pemelajar tingkat dasar (low-achievers) tidak mampu menghasilkan teks deskriptif yang sesuai. Temuan-temuan tersebut menunjukkan bahwa tahapan menulis yang dilakukan oleh pemelajar tingkat lanjut (high-achievers) dan pemelajar tingkat menengah (middle-achievers) dalam proses menulis memengaruhi kualitas teks deskriptif yang dibuat, sedangkan tahapan menulis yang dilakukan oleh para pemelajar tingkat dasar (low-achievers) dalam proses menulis tidak memengaruhi kualitas teks deskriptif yang dibuat. Berdasarkan temuan-temuan yang didapat dalam penelitian ini, penulis menyarankan agar kurikulum dan silabus yang digunakan dalam mata kuliah menulis di Jurusan Bahasa Inggris perlu lebih menyasar pada proses menulis pemelajar karena tahapan menulis yang runut dapat memengaruhi kualitas tulisan yang dibuat. Selain itu, program pelatihan menulis yang intensif juga diperlukan baik untuk pemelajar dan pendidik agar semua hambatan ketika menulis dapat diminimalisasi. Kata-kata kunci: proses menulis (tahap pra menulis, tahap menulis, tahap pasca menulis) dan teks deskriptif.